Competence and Performance Aspects in the Placement of the Head of Financial Affairs at the North Kalimantan Police Work Unit - Faesal Rachmat; Eko Prasojo (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
The Indonesian National Police as well as other organizations in the era of the industrial revolution 4.0 are also faced with various challenges. The main task of the National Police as a protector, protector, and servant of the community, maintaining security and public order and law enforcement will be more complex in the future due to the rapid advancement of information technology. This study aims to analyze aspects of competence and performance in the placement of the head of financial affairs at the North Kalimantan Regional Police Work unit. The research method used is descriptive qualitative with data collection techniques, namely interviews and documentation. The informants in this study were 5 personnel who served in the Itwasda work unit, Ditresnarkoba, Bidpropam, Biddokkes, and Yanma Regional Police North Kalimantan. Data analysis techniques, namely data reduction, data presentation, and conclusion drawing. The results of the study showed that personnel with the rank of Brigadier General who was appointed to the position of Kaurkeu even though they were with temporary stakeholder status, were still able to run well. This can be seen from the well-running of police activities at the Regional Police North Kalimantan, especially in the Work units at the Regional Police North Kalimantan. This of course cannot be separated from the role of financial managers in each work unit. Even with the rank of First Brigadier, the personnel appointed to the Kaurkeu position were able to show good performance. Although from interviews conducted with them, it was found that the five of them did not have an educational background related to finance, either in general or specifically in managing police finances. They only study independently under the guidance of the Regional Police's financial advisory function, namely the Bidkeu Regional Police. However, 4 of the 5 personnel have certificates as treasurers from State Treasury Service Office Tanjung Selor. Thus, it can be concluded if the deficiency in the competency factor can be covered by the existence of social support.